Peningkatan Kinerja Manajemen Pendidik dan Tenaga Kependidikan untuk Mewujudkan Sekolah Unggul di SMPN 15 Gresik - Anggraini, Della Rana Maulidia; Mazidah, Ifrochaini Al; Windasari, Windasari (Lembaga Yasin AlSys, 2024)
This research aims to analyze strategies that can improve the performance of teaching staff and education staff at SMPN 15 Gresik. The research method used is a case study with a qualitative research approach. Data was obtained through observation, interviews and document analysis. The findings show that the implementation of professional training and development, welfare development, as well as improving learning facilities and environments are the main factors in improving the performance of teaching and education staff. The results of this research can contribute to school administrators in designing effective strategies to improve the quality of education at SMPN 15 Gresik.